CRISTALLISING A CONCEPT: A BIBLIOMETRIC ANALYSIS OF CORPORATE SOCIAL RESPONSIBILITY AND SUSTAINABILITY - Casiana Ille (Annals of the University of Oradea: Economic Science, 2021)
Corporate Social Responsibility (CSR) is still a developing domain both in study and practice surrounded by a lot of confusion as many authors have previously shown despite the considerable broad spectrum of approaches. Starting with the Ancient times and until nowadays, the notion has displayed sometimes chameleonic features and there are still discussions regarding a consensus on the topic. While the CSR concept can be traced back to Ancient times and contoured in the 1950’s, the Corporate Sustainability (CS) concept can only be traced to the late 1980s when the concept of sustainable development (SD) was gaining momentum, as research conducted in the field has shown. Both CSR and corporate sustainability (CS) concepts have been in the spotlight in the last two decades and some researchers even use the terms interchangeably while others argue that the terms are different: similar, but not the same. Other authors dispute that each concept has a different origin that unravels a distinct pathway but they have both focalized on the same spot, using similar definitions, assumptions, same networks and measurement. More recent research suggests that CSR should be regarded and integrated as a component of CS strategy either as a transitional step or the final one for the business rather than keeping the two concepts on different pathways. Even though the concepts are brought lately more together, the common theoretical aspects need more attention and a thorough discussion, some authors argue. Therefore, this research proposes a bibliometric analysis of the existing literature on CSR and CS during the past three decades since the globalisation of the terms. The approach of this study is comparative, seeking to picture the evolution of the global interest on the subject compared to the focus of the Romanian research regarding CSR and CS and SD.